2006
DOI: 10.1074/jbc.m600054200
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Domains for Anti- and Pro-apoptotic Activities of IEX-1

Abstract: IEX-1 (immediate early response gene X-1) is a stress-inducible gene. Its overexpression can suppress or enhance apoptosis dependent on the nature of stress, yet the polypeptide does not possess any of the functional domains that are homologous to those present in well characterized effectors or inhibitors of apoptosis. This study using sequence-targeting mutagenesis reveals a transmembranelike integrated region of the protein to be critical for both pro-apoptotic and anti-apoptotic functions. Substitution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 40 publications
9
60
0
Order By: Relevance
“…IEX-1 as well as its rodent homologues PRG1 and gly96 represent short-lived proteins consisting of 156, 160 and 153 amino acids, respectively, and, to current knowledge, share no significant sequence similarities with any other known protein. Depending on cell type and stimulus-specific conditions, IEX-1 regulates cell growth and cellular viability (reviewed in Wu, 2003), and a significant apoptosis triggering effect by IEX-1 has been described (Scha¨fer et al, 1999;Arlt et al, 2001;Grobe et al, 2001;Schilling et al, 2001;Osawa et al, 2003;Shen et al, 2006). In the present study, we identified IEX-1 as an important mediator of G17-dependent NFkB inhibition and apoptosis in Colo320 cells expressing the wild-type CCK2 receptor.…”
Section: Introductionsupporting
confidence: 51%
“…IEX-1 as well as its rodent homologues PRG1 and gly96 represent short-lived proteins consisting of 156, 160 and 153 amino acids, respectively, and, to current knowledge, share no significant sequence similarities with any other known protein. Depending on cell type and stimulus-specific conditions, IEX-1 regulates cell growth and cellular viability (reviewed in Wu, 2003), and a significant apoptosis triggering effect by IEX-1 has been described (Scha¨fer et al, 1999;Arlt et al, 2001;Grobe et al, 2001;Schilling et al, 2001;Osawa et al, 2003;Shen et al, 2006). In the present study, we identified IEX-1 as an important mediator of G17-dependent NFkB inhibition and apoptosis in Colo320 cells expressing the wild-type CCK2 receptor.…”
Section: Introductionsupporting
confidence: 51%
“…IER3 protects from Fas-or TNF-␣-induced apoptosis, and its overexpression can suppress or enhance apoptosis, depending on the nature of stress (22). This gene is also thought to play a critical role in the regulation of intracellular ROS homeostasis (23). Finally, the gene encoding PPP1R15A (protein phosphatase 1, inhibitory subunit 15A) also appeared in this cluster.…”
Section: Resultsmentioning
confidence: 94%
“…The immediate early responsive gene X-1 (IEX-1) has a pivotal role in regulation of mitochondrial F 1 F 0 -ATPase activity, in protection against apoptosis, and in resolution of inflammation. [13][14][15] Null mutation of IEX-1 enhanced apoptosis, 16 reduced ATP synthase activity, 17 and prolonged inflammatory responses in a tissue-dependent manner in mice. 15,18 Furthermore, IEX-1 is upregulated by NF-kB and in turn inhibits NF-kB activation as a negative feedback mechanism contributing to inflammation resolution.…”
Section: Traumatic Brain Injury (Tbi) Represents a Serious Public Healthmentioning
confidence: 99%